Distribution Range of Toadfishes Opsanus Rafinesque, 1818 (Batrachoididae) in the Western Atlantic, with Emphasis in the Introduction of O. beta in Brazil - Roman Miiller, Natali Oliva; de Carvalho, Barbara Maichak; Camargo Figueiredo, Marcus Vinicius; Aguilar-Perera, Alfonso; Vitule, Jean Ricardo Simões (Thalassas : revista de ciencias del mar, 2023)
Toadfishes (Batrachoididae) are composed by 83 species, in 23 genera, which inhabit marine and estuarine habitats in tropical and subtropical areas worldwide. Seven genera, in 23 species, inhabit the western Atlantic Ocean, with the genus Opsanus Rafinesque, 1818 showing five species with a native distribution in the Gulf of Mexico and Caribbean Sea: Opsanus beta (Goode & Bean 1880), O. dichrostomus Collette, 2001, O. pardus Collette, 2001, O. phobetron Walters & Robin, 1961, and O. tau (Linnaeus, 1766). In this work, we compiled scientific literature, and searched database through internet, on the geographic distribution range and life history aspects of Opsanus species, with emphasis on the introduced O. beta in Brazil. Opsanus beta showed an updated geographic distribution beyond its native range, with an established population in estuaries of Brazil. O. tau showed a record off the Canadas’s coast, without evidence of population establishment. Other Opsanus species are still recorded in their native, geographic distribution range. However, these species have potential for invasions, dispersing to other geographic areas due to their predatory and generalist characteristics and life history, in combination with anthropogenic factors, which may favor a high adaptability to new environments. In Brazil, O. beta is widely recognized as introduced species in estuaries, but no studies have described its ecological impacts on the native marine fauna yet. We recommend a long-lasting monitoring of Opsanus species, outside its native geographic distribution, to understand their dispersion and adaptation to new environments.